Hospital merger control in Germany, the Netherlands and England: Experiences and challenges. Issue 1 (January 2016) - Schmid, Andreas; Varkevisser, Marco
Highlights: Germany, the Netherlands and England have hospital competition. Hospital competition requires robust competition policy, including hospital merger control. The German antitrust authority focuses on maintaining the preconditions for competition. In the Netherlands, there is a strong focus on hypothesized countervailing buyer power. In England, currently the most comprehensive analysis of proposed mergers is observed. Abstract: Aiming at the efficiency enhancing and quality improving effects of competition, various steps have been undertaken to foster competition in hospital markets. For these mechanisms to work, robust competition policy needs to be enacted and enforced. We compare the hospital markets in Germany, the Netherlands and England regarding their experience with competition and put a special focus on merger control and the stringency of its implementation. Elaborating on the differences in merger control practice we find that despite very similar goals the respective agencies apply very different approaches and take fundamentally different routes when balancing proclaimed benefits of mergers with potential risks of consolidated markets. While the German competition authority has a strong focus on maintaining the preconditions for competition, in the Netherlands we find over the past decade a much stronger focus on hypothesized countervailing buyer power, accepting in turn highly concentrated markets. In England we find the currently most comprehensive analysis of proposed mergers in combination with a clearly positive assessment of the effects of patient choice and competition on prices and quality. All agencies are still reluctant to implement merger simulation models or similarly advanced econometric methods in their appraisal. One very likely reason is a lack of country specific empirical evidence on these matters.